Analisis Faktor-Faktor yang Mempengaruhi Ekspor Crude Palm Oil (CPO) di Provinsi Kalimantan Selatan - Freddy Siahaan; Ali Wardhana (PPJP Universitas Lambung Mangkurat, 2022)
This study aims to determine the factors that affect crude palm oil exports in South Kalimantan province, knowing the influence of production amount, dollar exchange rate, and CPO price on CPO exports in South Kalimantan Province. In increasing CPO production for the future, Indonesia is still superior because of the availability of sizeable tropical land for planting oil palm trees. Indonesia's CPO production, especially in South Kalimantan, continues to increase. It can be identified because of the influence of the amount of output, dollar exchange rate, and CPO price on South Kalimantan CPO exports?This research is research that uses multiple linear regression analysis techniques. Linear regression is one of the statistical tools used to describe the relationship between variables; the dependent and independent variables are used. The results showed that the amount of production (X1)) and the exchange rate of the Dollar (X3) together did not significantly influence the CPO Export of South Kalimantan (Y).